2019
DOI: 10.1007/s00256-019-03206-z
|View full text |Cite
|
Sign up to set email alerts
|

CT radiation dose reduction in patients with total hip arthroplasties using model-based iterative reconstruction and orthopaedic metal artefact reduction

Abstract: ObjectiveTo evaluate the impact of radiation dose reduction on image quality in patients with metal-on-metal total hip arthroplasties (THAs) using model-based iterative reconstruction (MBIR) combined with orthopaedic metal artefact reduction (O-MAR).Materials and methodsPatients with metal-on-metal THAs received a pelvic CT with a full (FD) and a reduced radiation dose (RD) with −20%, −40%, −57%, or −80% CT radiation dose respectively, when assigned to group 1, 2, 3, or 4 respectively. FD acquisitions were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Although several approaches were suggested to reduce the artifacts caused by prostheses, including the optimization of single-energy CT scanning (14), iterative reconstructions, and specific software for iterative metal artifact reduction (18,19), these techniques can generate new artifacts, such as blurring and shape distortion (20-26). Moreover, in the study by Bamberg et al ( 23), image quality with DECT was superior to that with single-energy CT in 29 of 31 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although several approaches were suggested to reduce the artifacts caused by prostheses, including the optimization of single-energy CT scanning (14), iterative reconstructions, and specific software for iterative metal artifact reduction (18,19), these techniques can generate new artifacts, such as blurring and shape distortion (20-26). Moreover, in the study by Bamberg et al ( 23), image quality with DECT was superior to that with single-energy CT in 29 of 31 cases.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the methods for reducing the CT radiation dose include reducing the tube voltage, reducing the tube current, shortening the scanning time, and applying iterative algorithms. 14,15 Liu et al 12 proved that low-dose CT scanning technology (100 kVp) in renal CTA examination can significantly decrease ED, by 37.24%. However, we chose 80 kVp in the present study, further reduced the tube voltage, and decreased ED by approximately 50.54%.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting this type of postoperative protocol that includes multiple follow-up CT scans further highlights the importance of minimizing radiation exposure in this patient population [15]. Recently introduced advanced MAR techniques have not only shown substantial benefit in reducing artifact compared with standard CT techniques when imaging patients with arthroplasties, including TSAs [23,24] and reverse shoulder arthroplasties [25], but have also shown the potential to reduce the high radiation exposure associated with standard MAR CT techniques (generally in phantom studies) [5][6][7]. The purpose of this study, therefore, was to determine whether a lower-dose protocol using an advanced MAR CT technique could be used in a clinical setting to evaluate bone and soft tissue structures adjacent to hardware without compromising the ability to detect pathology.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one human study has assessed reduced-dose and full-dose CT in patients with metal-onmetal hip arthroplasties using an advanced MAR technique from a single vendor [7]. This study found that subjective image quality with reduced-dose CT was significantly worse than with full-dose CT. We have found no other reports of clinical studies evaluating low-dose MAR CT for other types of implants or using other MAR techniques.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation